Given that ( 1 + 2 x ) n = i = 0 ∑ n a i x i , if i = 0 ∑ n a i = 2 4 3 , find the value of i = 0 ∑ n i + 1 a i .
The answer is q p , where p , q are positive coprime integers. Submit p + q .
Note: Try solving it without using binomial theorem .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Substituting x = 1 yields 3 n = 1 = 0 ∑ n a i = 2 4 3 which implies n = 5 .
Hence integrating on both sides from 0 to 1 yields ∫ 0 1 ( 1 + 2 x ) 5 d x = i = 0 ∑ 5 i + 1 a i = 3 1 8 2 hence making the answer 1 8 5 .
Yeah, that's a good solution. Mine is similar as yours except using the anti-derivative.
Same approach
Problem Loading...
Note Loading...
Set Loading...
Given that ( 1 + 2 x ) n = i = 0 ∑ n a i x i and ( 1 + 2 ) n = i = 0 ∑ n a i = 2 4 3 = 3 5 ⟹ n = 5 . Now we have:
i = 0 ∑ 5 a i x i i = 0 ∑ 5 i + 1 a i x i + 1 i = 0 ∑ 5 i + 1 a i = ( 1 + 2 x ) 5 = ∫ ( 1 + 2 x ) 5 d x = ∫ 0 1 ( 1 + 2 x ) 5 d x = 2 1 ∫ 1 3 u 5 d u = 2 1 [ 6 u 6 ] 1 3 = 1 2 3 6 − 1 = 3 1 8 2 Integrate both sides w.r.t. x Putting x = 1 Let u = 1 + 2 x ⟹ d u = 2 d x
Therefore p + q = 1 8 2 + 3 = 1 8 5 .